Use of natural anti-oxidants in experimental animal models of hepatic ischemia-reperfusion injury. (December 2020) - Kyriakopoulos, Georgios; Valsami, Georgia; Tsalikidis, Christos; Pitiakoudis, Michail; Tsaroucha, Alexandra K.
Abstract: Background: Ischemia-reperfusion injury (IRI) remains a clinical challenge in liver surgery, trauma and transplantation, contributing to morbidity and mortality worldwide. Thus, its impact, not only on the liver itself but also on remote tissues, has been studied during the last years. Different natural anti-oxidant substances have been researched in animal models, implementing different times of ischemia, aiming to test new therapeutic interventions. Objective: A literature review has been conducted with two goals: (1) to identify different natural anti-oxidants studied in experimental models; and (2) to summarize the various times of ischemia employed. Methods: Scientific papers published in PubMed for the period 2000–2020 were searched and reviewed. Results: More than 30 natural anti-oxidants have been tested. The time of ischemia ranged from 15 to 90 min with 60 min used most frequently, followed by 45 min. No studies were found with time exceeding 90 min. Conclusions: A significant number of research has been conducted on the use and protective effect of natural anti-oxidants in experimental animal models. Based on the published papers, 45–60 min seems to be the optimal duration of ischemia. Highlights: Liver IRI is a multifactorial and complex process, involving many mechanisms, cells and mediators. Even though, most of these mechanisms have not been completely understood, several substances have been tested in experimental models in order to determine their protective or destructive role. Antioxidant therapy is a promising therapeutic pathway that can ameliorate the impact of liver ischemia-reperfusion injury. Non-pharmaceutical, natural extracts are increasingly gaining their place into the therapeutic options of physicians, in an attempt to avoid various adverse effects that the chemical drugs can cause. New unexplored research areas may include different strains of rats, more studies in larger mammals of comparable anatomy to humans, experiments on different liver diseases, publishing negative results regarding toxic doses of natural antioxidants, and testing different ischemia times.